2015
DOI: 10.1007/s12035-015-9186-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of High-sensitivity C-Reactive Protein at Admission Are More Strongly Associated with Poststroke Depression in Acute Ischemic Stroke than Homocysteine Levels

Abstract: Inflammatory processes have fundamental roles in depression. The primary purpose of this study was to assess the serum levels of high-sensitivity C-reactive protein (Hs-CRP) and homocysteine (HCY) at admission to the presence of poststroke depression (PSD). From December 2012 to December 2013, first-ever acute ischemic stroke patients who were admitted to the hospital within the first 24 h after stroke onset were consecutively recruited and followed up for 6 months. Serum levels of Hs-CRP and HCY were tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…The influence of hs-CRP on ischemic stroke has been well established, and hs-CRP has been reported as a predictor of disease severity, prognosis and mortality in patients with ischemic stroke [19, 29]. Furthermore, high plasma hs-CRP levels are associated with clinical complications following acute ischemic stroke [18, 30] PMD, which may result in severe morbidity, commonly occurs in patients with PAI during the acute stage. This is the first study to explore the relationship between hs-CRP and PMD in patients with penetrating artery ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of hs-CRP on ischemic stroke has been well established, and hs-CRP has been reported as a predictor of disease severity, prognosis and mortality in patients with ischemic stroke [19, 29]. Furthermore, high plasma hs-CRP levels are associated with clinical complications following acute ischemic stroke [18, 30] PMD, which may result in severe morbidity, commonly occurs in patients with PAI during the acute stage. This is the first study to explore the relationship between hs-CRP and PMD in patients with penetrating artery ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that high-sensitivity C-reactive protein (hs-CRP) may act as an inflammatory factor that responds to ischemic stroke [18, 19]. A high hs-CRP level has been found to show predictive value for poststroke depression [18] and poor outcome [1922] in ischemic stroke patients. The levels of hs-CRP may be associated with the risk of excessive ischemic stroke independently [23].…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Post-stroke depression (PSD) may have a similar pathological process to depression. Previous research has shown that the levels of some molecular markers are changed in the peripheral system of PSD patients, including C-reactive protein (CRP) and homocysteine, 5 7 brain-derived neurotrophic factor (BDNF), 8 and triiodothyronine. 9 Of these pathophysiological factors, oxidative and nitrosative stress pathways are believed to be the most crucial pathophysiological factors, 10 since the brain has high metabolic rates and low antioxidant levels.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hu et al reported in a retrospective study of more than 300 patients that in conjunction with platelet to lymphocyte ratio, admission NLR is associated with depression at six months after stroke [47] An important mechanism which leads to the occurrence of depression is low grade inflammation which may have an impact in dopaminergic systems [53]. A study by Tang et al illustrated that among patients with ischemic stroke, high sensitivity CRP (hsCRP) obtained during admission has been shown to correlate with depression at six months post stroke [54].…”
Section: Ischaemic Cascade and Inflammationmentioning
confidence: 99%